EDUCATION OF YOUTH IN THE SPIRIT OF MILITARY PATRIOTISM (Academia Science Repository, 2023)
In this article, the young generation in our country to the Motherland about educating in the spirit of love, forming a sense of patriotism in young people it is about concepts, views.